Analisis Peramalan Harga Telur Ayam Ras Dengan Menggunakan Metode SARIMA - Hakim, Ilham Luqman; Sanglise, Marlinda; Suhendra, Christian Dwi (JURNAL MEDIA INFORMATIKA BUDIDARMA, 2024)
Eggs are a widely favored source of animal protein. One commonly consumed type is chicken eggs. Besides being easy to prepare, a notable advantage of chicken eggs is their affordability compared to other sources of animal protein. However, chicken eggs are subject to price fluctuations at specific times, such as religious holidays. These fluctuations can lead to losses for both producers and consumers. One way to address this issue is by forecasting. Forecasting is crucial as it provides estimated price information for the future. With this information, producers and consumers can prepare appropriate strategies to cope with price changes. The price of chicken eggs fluctuates periodically, thus the method employed in this research is Seasonal Autoregressive Integrated Moving Average (SARIMA). SARIMA is a forecasting method specifically used for data exhibiting seasonal patterns. Based on the results of this study, the best SARIMA model obtained is , demonstrating excellent performance with an RMSE value of 1491.30 and a MAPE of 3.40%. From this model, forecasted prices of chicken eggs in the traditional market of Manokwari city for the next 12 months are obtained, spanning from March 2024 to February 2025. According to the forecast results, the price of chicken eggs is expected to rise in March to June 2024 and December 2024 to January 2025.